2021
DOI: 10.21037/tlcr-20-1263
|View full text |Cite
|
Sign up to set email alerts
|

Impact of docetaxel plus ramucirumab on metastatic site in previously treated patients with non-small cell lung cancer: a multicenter retrospective study

Abstract: Background: Docetaxel (DOC) plus ramucirumab (RAM) has been recommended as an optimal therapy for previously treated patients with non-small cell lung cancer (NSCLC). In a clinical setting, there are few reports about DOC plus RAM, therefore its effect on factors such as Eastern Cooperative Oncology Group (ECOG) performance status (PS) and metastatic sites is still unknown. Methods:We recruited NSCLC patients who received DOC plus RAM in four medical facilities in Japan from June 2016 to March 2020. We retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The comparative clinical trial of DTX/RAM versus placebo/DTX or the REVEL trial showed survival benefits as a second-line treatment of stage IV non-small cell lung cancer (NSCLC) after disease progression on platinum-based therapy [ 7 ]. Recent studies have also revealed the efficacy of the DTX/RAM combination therapy in patients with a history of ICI treatment [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Although the combination of chemotherapy and ICIs is currently becoming the standard regimen as the first-line treatment of advanced NSCLC, there is an insufficient number of studies regarding the use of chemotherapy and ICI combination as a second-line or later-line therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The comparative clinical trial of DTX/RAM versus placebo/DTX or the REVEL trial showed survival benefits as a second-line treatment of stage IV non-small cell lung cancer (NSCLC) after disease progression on platinum-based therapy [ 7 ]. Recent studies have also revealed the efficacy of the DTX/RAM combination therapy in patients with a history of ICI treatment [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Although the combination of chemotherapy and ICIs is currently becoming the standard regimen as the first-line treatment of advanced NSCLC, there is an insufficient number of studies regarding the use of chemotherapy and ICI combination as a second-line or later-line therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that ECOG‐PS = 2 is a poor prognostic factor for docetaxel alone or docetaxel plus ramucirumab therapy in previously treated patients with NSCLC. 25 , 26 We retrospectively demonstrated that a poor PS (ECOG‐PS = 2) was an independent prognostic factor for PFS and OS in the second‐line setting after chemoimmunotherapy. Therefore, the decision to use second‐line therapy following chemoimmunotherapy for NSCLC patients with a poor PS should be made with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have retrospectively analyzed RAM and DOC combination therapy [11][12][13][14][15]. Harada et al demonstrated that the PFS of patients who received RAM and DOC after ICI was more than twice that of those who did not, showing a signi cant difference (5.7 months vs. 2.3 months, p = 0.020) [13].…”
Section: Introductionmentioning
confidence: 99%